RANCANG BANGUN APLIKASI SIMULASI REKAM MEDIK INSTALASI RAWAT JALAN PADA STIKES YAYASAN RS. Dr. SOETOMO SURABAYA - Irawan, Andrian Chandra; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
STIKES Yayasan RSUD Dr. Soetomo Surabaya is a private university under the auspices of the Yayasan RSUD Dr. Soetomo Surabaya. Evolving from APIKES PENA HUSADA SURABAYA, Akademi Rekam medik dan Informatika Kesehatan. To improve the quality of education , then STIKES Yayasan RSUD Dr. Soetomo conduct simulation courses hospital records activity on Prodi D3 Rekam Medik dan Informasi Kesehatan . This course is required because when working in a hospital , a medical record should make reports in accordance with existing standards . As a supporter of the course , the STIKES Foundation Hospital Dr. Soetomo have an application that is used to simulate the activities of hospital records . The application simulates the activities of the medical records of inpatient , outpatient visits and Emergency Room ( ER ).But in use, the application is considered not relevant to the curriculum Buku Petunjuk Pengisian, Pengolahan dan Penyajian Data Rumah Sakit serta Sistem Pelaporan Rumah Sakit Revisi VI. In the existing applications , registration services in each poly less specific. This specification is needed so that a student can have a more concrete picture of the medical record of activities that take place in hospitals and can generate reports of medical records hospital activity report ( RL 3 ) for the activities of obstetrics and perinatology .In addition , this application does not have the support of the International Classification of Disease ( ICD - 10 ) . Support for the International Classification of Disease ( ICD - 10 ) is required to allow students to make a report on the statistical information of morbidity and mortality in a hospital . Also this application can not serve queue between the clinic in parallel and there is no division of permissions for each user . Service queue in parallel and sharing permissions needed so teachers can conduct role play simulation medical record.Based from the problems, STIKES Yayasan RSUD Dr. Soetomo requires Simulation Application in the Medical Records STIKES Hospital Foundation . Dr. Soetomo which can serve transactions at each clinic with a more specific type of service , so as to generate the required reports and to support the International Classification of Disease ( ICD - 10 ) used for the benefit of statistical information of morbidity and mortality . Applications and reports are used to allow students to have an overview of the applications and reports that exist in the world of work